Estimation of TNF- α and some immunological parameters in patient with systemic lupus erythematosus - AL-abdullah, sarah; Murtada Hafedh Hussein (University of Thi-Qar Journal of Science, 2024)
Abstract: Abstract— Systemic Lupus Erythematosus (SLE) is a multifactorial chronic systemic autoimmune disease. It is characterized by a lack of immune tolerance to autoantigens such as nuclear antigens. In this study, 25 individuals diagnosed with SLE had their blood samples drawn, while 25 healthy individuals were used as a control group. The results of this investigation show that the patients’ TNF-α levels (106.9 ± 10.8) significantly increased more than 52.86 in the control group. Comparing the immunological parameters of the patients to the healthy group, the study revealed a decrease in the eosinophile, basophile, lymphocyte, and monocyte counts (010 ± 0.003, 0.022 ± 0.004, 1.71 ± 0.66, 0.21 ± 0.047 respectively) and a rise in the neutrophile and immature granulocyte counts (7.43 ± 1.66, 2.68 ± 0.46 respectively) in SLE patient. Keywords— SLE,TNF‑α,immunological parameters